2006
DOI: 10.1158/0008-5472.can-06-0448
|View full text |Cite
|
Sign up to set email alerts
|

Selective Antitumor Effect of Novel Protease-Mediated Photodynamic Agent

Abstract: A new approach to selective photodynamic therapy (PDT) was developed by designing chlorin e6 (Ce6)-containing macromolecules, which are sensitive to tumor-associated proteases. The agents are nontoxic in their native state but become fluorescent and produce singlet oxygen on protease conversion. Coupled with optimized delivery systems, we show that (a) the agents efficiently accumulate in tumors due to the enhanced permeability and retention effect, (b) the agents are locally activated by proteases, (c) local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
128
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 20 publications
2
128
0
1
Order By: Relevance
“…[8][9][10] A recent PDT study using macrophage-targeted photosensitizers preliminarily demonstrated the viability of near-infrared lightactivated therapeutic nanoagents in the treatment of atherosclerotic vascular disease by showing preferential destruction of macrophages in vitro and in mouse atheromata. 11 Choi et al 12 developed a novel protease-mediated photodynamic agent that allowed visualization of targets and local drug concentration before exerting selective antitumor effects on light illumination: L-SR15 CatB activatable photosensitizers that are nontoxic in their native state but become fluorescent and produce singlet oxygen on protease conversion followed by light therapy. In our recent study, using the RAW 264.7 macrophage cell line, we showed that intracellular uptake of L-SR15 and subsequent activation of the theranostic nanoagent by proteolytic cleavage could induce cell death on light illumination; the macrophage cell death was interfered by commonly prescribed cardiovascular drugs with antioxidant effects: atorvastatin and clopidogrel.…”
mentioning
confidence: 99%
“…[8][9][10] A recent PDT study using macrophage-targeted photosensitizers preliminarily demonstrated the viability of near-infrared lightactivated therapeutic nanoagents in the treatment of atherosclerotic vascular disease by showing preferential destruction of macrophages in vitro and in mouse atheromata. 11 Choi et al 12 developed a novel protease-mediated photodynamic agent that allowed visualization of targets and local drug concentration before exerting selective antitumor effects on light illumination: L-SR15 CatB activatable photosensitizers that are nontoxic in their native state but become fluorescent and produce singlet oxygen on protease conversion followed by light therapy. In our recent study, using the RAW 264.7 macrophage cell line, we showed that intracellular uptake of L-SR15 and subsequent activation of the theranostic nanoagent by proteolytic cleavage could induce cell death on light illumination; the macrophage cell death was interfered by commonly prescribed cardiovascular drugs with antioxidant effects: atorvastatin and clopidogrel.…”
mentioning
confidence: 99%
“…58 It accumulates in the tumor and is selectively activated by Cathepsin B. Ce6 is a photodynamic agent and in theory can, apart from imaging, be used for therapeutic purposes as well. When it is illuminated by an appropriate wavelength it transfers its energy to a neighboring molecular oxygen, producing cytotoxic singlet oxygen which causes selective tissue damage, the fundamental principle of photodynamic therapy.…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…When it is illuminated by an appropriate wavelength it transfers its energy to a neighboring molecular oxygen, producing cytotoxic singlet oxygen which causes selective tissue damage, the fundamental principle of photodynamic therapy. 58 In mice bearing fibrosarcomas on the hind limb, protease-mediated photodynamic therapy selectively suppressed tumor growth by >50%. When Ce6 is used on its own, it is not very selective, and may cause damage to normal cells as well.…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…Activatable or ''smart'' optical probes are appealing because they only fluoresce when bound to their target site (1)(2)(3)(4)(5)(6). Several strategies have emerged to create such smart optical probes.…”
Section: Introductionmentioning
confidence: 99%